Global Talent Retention: Understanding Employee Turnover Around the World - Allen, David G. (David Gray); Vardaman, James M. (Professor of management) (Talent management, 2021)
Through extensive research Global Talent Retention: Understanding Employee Turnover Around the Worldaddresses the need for turnover theory and research to give more careful consideration to global and cross-cultural perspectives on employee retention, and includes contributions from a global range of scholars.